Antibacterial and Cytotoxic Activity from Ethyl Acetate Extract of Sargassum from Kabung Island West Kalimantan - Jumlia; Mega Sari Juane Sofiana; Anthoni Batahan Aritonang; Warsidah Warsidah; Rita Kurnia Apindiati; Ikha Safitri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Sargassum belongs to Phaeophyceae is widely distributed in Indonesian waters, including Kabung Island. Seaweed has bioactive compounds that potential to be developed. In the health sector, one of the global problems that still increasing is the bacterial infection. This condition leads us to explore antibiotic from natural resources to overcome this problem. Sargassum grow abundantly in the waters of Kabung Island and this genus has not been utilized by local community. For this reason, the aim of this study is to evaluate the antibacterial and cytotoxic activity from ethyl acetate extract of Sargassum from Kabung Island, West Kalimantan. Antibacterial activity test of the ethyl acetate extract against E. coli and S. aureus was conducted using the diffusion method with concentration series of 100; 50; 25; 5; 1; and 0.1 g/mL. While, the assessment of cytotoxic activity was carried out with concentration of 10; 100 and 1000 g/mL. The result showed that ethyl acetate extract of Sargassum from Kabung Island only showed antibacterial activity against E. coli bacteria. The greatest inhibition zone was 11.59 mm at a concentration of 100 g/mL, while in the cytotoxic test exhibited that the LC50 was more than 1000 ppm, so it was considered into non-toxic category.